ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PROGRAM LINEAR DENGAN PROSEDUR NEWMAN - Dinda Rahmawati; Laelatul Dhian Permata (Jurnal Pembelajaran Matematika, 2018)
Abstract: One of the mathematics materials in high school is a linear program. The problems associated with a linear program are usually presented in a story problem. Based on the report of national exam results by Puspendik 2017 that the percentage of mastery of math problems subjects national exam SMA N I Wonosari in solving problems associated with linear program is equal to 52.78%. The data shows that there are still many students who make mistakes on linear program material. To overcome these problems, it is necessary an analysis to be able to know the types of mistakes made by students. This study aims to analyze students' errors in solving the story problem on linear program materials using Newman analysis. This research uses descriptive analysis method. The subjects of this study are 15 students of class XI SMA N 1 Wonosari Lesson Year 2017/2018. Data collection is done by test method. Based on data analysis result using Newman's error analysis procedure, it is concluded that students do (1) reading errors of 23.33%, (2) comprehension errors of 81.67%, (3) transformation errors of 30%, (4) process skills errors of 56.67%, (5) encoding errors of 66.67%. The type of mistake that students often make is not to write down what is known and what is asked in the question, which results in a student's mistake in writing the conclusion. Error analysis can be used to determine the location of student error, so that can be used as a basis for consideration improvement of learning by teachers.Keywords: Newman, Story Problem, Program linear.